Nikolai Gogol’s Literary Works, Tsar's Absolutism and Russian Cutural Life in the 19th Century: A Preliminary Note - Herdi Sahrasad; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2019)
This paper is to study and understand the work of Nikolai Gogol, and to learn what and to what extent Tsar's absolutism in Russia under the old regime, has influenced his work, as well as its impact on the social, cultural, political, and economic realities of Russia under the Emperor's powerful rule in 19th century. Here also revealed, to what extent the tragic human life in Gogol's work and how the efforts of the author to uphold the existence and dignity of themselves and their society are revealed in the story